Facial Nerve Meningioma: A Cause of Pediatric Facial Weakness. Issue 3 (March 2017) - Deep, Nicholas L.; Gnagi, Sharon H.; Carpentieri, David F.; Adelson, P. David; Weisskopf, Peter A.
Abstract : Objective: To present an unusual case of a temporal bone meningioma with intrafascicular spread throughout the temporal facial nerve from cerebellopontine angle (CPA) to stylomastoid foramen. Patient: Four-year-old female with progressive facial weakness and normal hearing. Main Outcome Measure: Clinical, radiological, and histopathological findings of temporal bone meningiomas. Results: A patient presented with progressive facial weakness and normal hearing. Imaging demonstrated a mass within the left internal auditory canal radiologically consistent with a schwannoma. Asymmetric enlargement with enhancement of the left facial nerve from CPA to the stylomastoid foramen suggested facial schwannoma. At surgery, gross tumor was noted in the internal auditory canal, the fallopian canal seemed expanded and the facial nerve was enlarged and had an irregular contour. Resection of the facial nerve from the CPA to just proximal to its exit at the stylomastoid foramen was necessary to achieve negative margins. Cable grafting was performed. The histopathologic diagnosis was transitional meningioma with intraneural growth throughout the length of the resected facial nerve segment. Conclusion: Meningiomas involving the temporal bone are exceedingly rare. We report a rare case of a child presenting with progressive facial weakness due to a presumed facial schwannoma spreading along the facial nerve throughout its intratemporal course that at surgery was found to be an intrafascicular CN VII meningioma.